Application of the Bolar exception: Different approaches in the EU - Dmytro Doubinsky (South Centre, 2025)
This Research Paper addresses the growing problem of access to essential medicines, focusing on the role of intellectual property rights, particularly patent rights, in restricting access by enabling pharmaceutical market monopolies that keep drug prices high. The paper explores the Bolar exception, a legal mechanism designed to allow generic drug manufacturers to seek regulatory approval before a patent expires, thus preventing the de facto extension of patent monopolies. The study examines the transformation of the Bolar exception from a specific legal case into a significant tool of intellectual property, commercial, and pharmaceutical law. The paper analyzes key international legal frameworks and European directives related to the Bolar exception and highlights divergent interpretations of the Exception in German and Polish case law. Through this comparative analysis, the paper argues for the broader implementation of Bolar exceptions to improve access to affordable medicines and reduce healthcare costs.
Keywords: 300; Arzneimittel; Patentrecht; Generika; EU-Recht; EU-Staaten; Deutschland; Polen